1993
DOI: 10.7557/2.13.1.1070
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in density-dependent mortality and reproduction in Finnish reindeer

Abstract: Reindeer in the southern and central regions of reindeer husbandry in Finland feed on arboreal lichens or are given supplementary rations from midwinter whereas in the northern region reindeer use snow-covered forage throughout winter. Rates of mortality and reproduction were examined using data from population crashes of semi-domesticated reindeer that occurred in Northern Finland during 1960-1987. The mortality and reproductive rate were density-dependent in the southern region and the mortality was density-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…In addition to management actions that involve management of the local abundance of wolf and moose, re-introductions of wild forest reindeer into regions where the predation risk is lower is a noteworthy option to reduce the extinction risk of wild reindeer in Finland. Re-introductions can be an effective means of restoration (Bergerud & Mercer 1989, Kojola 1993. However, Bergerud and Mercer (1989) suggested that woodland caribou cannot return to their old natural ranges if there are high wolf numbers.…”
Section: Conservation and Management Implicationsmentioning
confidence: 99%
“…In addition to management actions that involve management of the local abundance of wolf and moose, re-introductions of wild forest reindeer into regions where the predation risk is lower is a noteworthy option to reduce the extinction risk of wild reindeer in Finland. Re-introductions can be an effective means of restoration (Bergerud & Mercer 1989, Kojola 1993. However, Bergerud and Mercer (1989) suggested that woodland caribou cannot return to their old natural ranges if there are high wolf numbers.…”
Section: Conservation and Management Implicationsmentioning
confidence: 99%
“…Since 1990, the wolf population in Finland has recovered significantly (Kojola et al 2004a(Kojola et al , 2006a, increasing from four family packs in 1996 to 25 packs in 2007 (Kojola 2007). Consequently, the expansion and the growth of the population have raised new challenges to wolf management objectives (Bisi et al 2007;Bisi and Kurki 2008).…”
Section: Introductionmentioning
confidence: 99%
“…If PA decreased the palatability of lichen tissue for reindeer, this would naturally enhance the survival of clones with highest PA concentrations and explain the observed higher PA concentrations in grazed sites. On the other hand, reindeer herding and the relatively high reindeer densities in Finnish Lapland are nowadays largely based on supplemental feeding during winter and the importance of lichen as fodder has decreased (Kojola and Helle 1993). Moreover, our study sites were located in reindeer summer grounds and, hence, unselective trampling may be of much greater significance than potentially selective grazing.…”
Section: Discussionmentioning
confidence: 99%